PERANCANGAN DAN IMPLEMENTASI PROTOTIPE WIRELESS POWER TRANSFER PADA SEPEDA MOTOR LISTRIK - Indra Hartarto Tambunan; Ester Yemima Br Bangun; I Gde Eka Dirgayussa; Angela Grace Gitarana Doloksaribu; Andreas Stephan Simanjuntak (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Advances in Wireless Power Transfer (WPT) system technology are increasingly being applied to the process of recharging battery packages for electric motorbikes. The battery package for an electric motorbike, 48 Volt 15 Ah, is used as a reference for the achievement target in this research. The WPT system is designed to be able to transfer or produce power equal to 10% of the battery package capacity. Utilization of Faraday's law which states that the number of turns in the transmitter and receiver coils used in the WPT system affects changes in flux and the amount of energy that can be transferred by the coil. In this paper, we will explain the WPT system experiments to compare system efficiency by changing the variables of coil diameter, number of coil turns, and distance between coils. Experiments show that the larger the coil diameter, the greater the output power on the receiver coil. The more turns the coil has, the greater the output power on the receiver coil, but the greater the distance between the coils, the smaller the output power on the receiver coil.